Where to from here? - Palmer, G W R (Victoria University of Wellington Law Review, 1995)
The author, a former politician and Prime Minister, provides a comment on the Treaty of Waitangi and the then-newly introduced Treaty Settlement process. The article is divided into two parts. The first part of the article asks what had been done since the signing of the Treaty, with Palmer arguing that the changing position of Māori in the New Zealand constitution was the most significant constitutional change. The second part of the article asks where New Zealand was headed next, arguing that Māori representation is (and always has been) a major issue. The author concludes that we would be better to concentrate on the very real complexities involved in getting to grips with the Treaty rather than marching off in some other direction to the beat of false drums.